Phase I study of humanized monoclonal antibody AVE1642 directed against the type 1 insulin-like growth factor receptor (IGF-1R), administered in combination with anticancer therapies to patients with advanced solid tumors. - Macaulay, V; Middleton, M; Protheroe, A; Tolcher, A; Dieras, V; Sessa, C; Bahleda, R; Blay, J; LoRusso, P; Mery-Mignard, D; Soria, J (2013)
BACKGROUND: Type 1 insulin-like growth factor receptor (IGF-1R) mediates resistance to chemotherapy and targeted agents. This study assessed the safety, pharmacokinetics (PK), and tolerability of humanized IGF-1R antibody AVE1642 with other cancer treatments. PATIENTS: Patients with advanced solid tumors received three weekly AVE1642 dosed at 6 mg/kg, chosen following previous study, with 75 (cohort A) or 100 mg/m(2) (B) docetaxel, 1250 mg/m(2) gemcitabine/100 mg erlotinib (C1), or 60 mg/m(2) doxorubicin (D1). Blood samples were assayed for PK, IGFs, and IGF-BP3. RESULTS: Fifty-eight patients received 317 AVE1642 infusions. The commonest adverse events were diarrhea (37/58 patients), asthenia (34/58), nausea (30/58), and stomatitis (21/58). Dose-limiting toxic effects in cohorts C1 (diarrhea) and D1 (neutropenia) prompted addition of cohorts C2 (1000 mg/m(2) gemcitabine/75 mg erlotinib) and D2 (50 mg/m(2) doxorubicin). Grade 3-4 hyperglycemia (three cases) accompanied steroid premedication for docetaxel administration. No PK interactions were detected. There were three partial responses in cohorts B (melanoma) and C (leiomyosarcoma, two cases) and 22 stabilizations ≥12 weeks, giving a control rate of 25/57 (44%). On treatment IGF-II rose by 68 ± 25 ng/ml in patients discontinuing treatment <12 weeks, and fell by 55.5 ± 21 ng/ml with disease control (P < 0.001). CONCLUSION: AVE1642 was tolerable with 75-100 mg/m(2) docetaxel and 1000 mg/m(2) gemcitabine/75 mg erlotinib, achieving durable disease control in 44%, with an association between IGF-II and response.